ALAT PEMANTAU SUHU JARAK JAUH BERBASIS SMS (AN SMS-BASED REMOTEe TEMPERATURE MONITORING DEVICE) - Jazi Eko Istiyanto; Eko Purwadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2005)
A remote temperature monitoring device based on the GSM (Global System for Mobile Communicatiobn) Short-Messaging Services (SMS) has been designed and constructed. The device is controlled by an AVR AT90S2313 microcontroller. Connected to the microcontroller are the temperature sensor and a cellular phone. A user, using another cellular phone, can query the status of the temperature by sending an SMS to the cellular phone attached to the microcontroller. Upon receiving the SMS, the device will read the SMS, interpret the SMS content as a command to access the temperature readings, compose a reply SMS and command the attached cellular phone to send the SMS to the querying cellular phone. The device has been implemented and tested on a series of Siemens cellular phones and has shown a good performance with the only predominant limitation being the availability and signal strength of the GSM infrastructure.